2019
DOI: 10.31234/osf.io/9deqk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Conspiracy Mentality in Denial of Science and Susceptibility to Viral Deception about Science

Abstract: Members of the public can disagree with scientists in at least two ways: people can reject well-established scientific theories and they can believe fabricated, deceptive claims about science to be true. Scholars examining the reasons for these disagreements find that some individuals are more likely than others to diverge from scientists due to individual factors such as their science literacy, political ideology, and religiosity. This study builds on this literature by examining the role of conspiracy mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Additionally, the lack of trust in governments is associated with a range of popular conspiracy beliefs (van Prooijen & Acker, 2015). Indeed, it is at the very nature of conspiracy mentality to be paranoid when it comes to authorities and distrustful of scientists, governments or international organizations (Landrum & Olshansky, 2019). This is why we expected the trust in institutions to negatively predict people's feelings of lacking control and thus lead to an increase in coronavirus-specific conspiracy beliefs.…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, the lack of trust in governments is associated with a range of popular conspiracy beliefs (van Prooijen & Acker, 2015). Indeed, it is at the very nature of conspiracy mentality to be paranoid when it comes to authorities and distrustful of scientists, governments or international organizations (Landrum & Olshansky, 2019). This is why we expected the trust in institutions to negatively predict people's feelings of lacking control and thus lead to an increase in coronavirus-specific conspiracy beliefs.…”
Section: Introductionmentioning
confidence: 93%
“…Although many of these CTs are clearly fanciful, such beliefs can also have negative implications for society. Apart from leading to distrust in political institutions, they can also lead to resistance to important medical and public health interventions (Ford et al, 2013;Landrum & Olshansky, 2019;Oliver & Wood, 2014). Examples include an unwillingness to receive vaccinations; rejection of conventional medical or dental treatments (e.g., use of fluoride); or possible gravitation towards unsupported and potentially dangerous treatments based on other belief systems (e.g., religious or pseudoscience; Ford et al, 2013;Douglas, Sutton, & Cichocka, 2017;Galliford & Furnham, 2017;Jolley & Douglas, 2017;Oliver & Wood, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that people who believe in a specific conspiracy theory are very prone to hold also other non‐related and even contradictory conspiracy beliefs (Miller, 2020; Wood et al, 2012), and they are much more likely to accept also various paranormal and pseudoscientific claims (e.g., Čavojová, Šrol, & Jurkovič, 2020; Lobato et al, 2014; Šrol, 2020). A study by Lewandowsky et al (2013); however, see Landrum & Olshansky, 2019) shows that conspiracist ideation – the tendency to explain complex societal and/or political events through conspiracy theories – may be the key factor in explaining the rejection of well‐established scientific findings, and subsequently, the endorsement of pseudoscientific beliefs. Based on this evidence, we wanted to examine whether people with stronger feelings of anxiety and lack of control concerning the COVID‐19 pandemic will only endorse more coronavirus‐specific conspiracy beliefs, or whether these feelings will be associated with reporting more generic (i.e., not coronavirus‐related) conspiracy, paranormal and pseudoscientific beliefs as well.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, conspiracy beliefs are known to be negatively associated with the trust in one's government (e.g., van Prooijen & Acker, 2015), as well as with interpersonal trust in general (Green & Douglas, 2018). Indeed, it is the very nature of conspiracist ideation to be paranoid when it comes to authorities and distrustful of scientists, governments, or international organizations (Landrum & Olshansky, 2019). This is why we expected the trust in institutions to negatively predict people's feelings of anxiety and lack of control and be associated with an increase in coronavirus‐specific conspiracy beliefs.…”
Section: Introductionmentioning
confidence: 99%